1994
DOI: 10.1038/eye.1994.156
|View full text |Cite
|
Sign up to set email alerts
|

The presentation of children with amblyopia

Abstract: SUMMARYThis study reports the presentation of 961 children who underwent amblyopia treatment at seven orthoptic centres in the United Kingdom. We confirmed previous authors' findings of a small but significant increased inci dence of left-sided compared with right-sided amblyopia overall. For pure anisometropic amblyopia this differ ence was very marked and a possible pathophysiological mechanism is proposed. The mean age of presentation for anismetropic, strabismic and mixed amblyopia was 5.6, 3.3 and 4.4 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
2
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 15 publications
7
34
2
3
Order By: Relevance
“…Similar findings have been reported in other studies as well (Repka et al, 2010;Woodruff et al, 1994). However, no clear explanation could be given to justify this unique laterality.…”
Section: Discussionsupporting
confidence: 78%
“…Similar findings have been reported in other studies as well (Repka et al, 2010;Woodruff et al, 1994). However, no clear explanation could be given to justify this unique laterality.…”
Section: Discussionsupporting
confidence: 78%
“…Anisometropic amblyopic patients apply to the hospital earlier than that of strabismic and mixed amblyopic children. Neither sex nor race affects the age of presentation according to them [10]. In the present study, the mean presentation age of the anisometropic children was 13.7 years old and the median age was 14 years old in the 5 -18 age group which was even older than the previous studies.…”
Section: Discussioncontrasting
confidence: 44%
“…OALib Journal was bigger than that of Woodruff et al [10]. We speculated this to the health care insufficiency of the city, which is in a geographically and socioeconomically difficult area.…”
Section: /10contrasting
confidence: 44%
See 1 more Smart Citation
“…Only 15% of anisometropic amblyopia was identified prior to the age of 5 years during a 4-year study in Leicestershire. 44 Woodruff and associates 45 found that the age of presentation for patients with anisometropic amblyopia (5.6 years) was much greater than that for patients with other types of amblyopia. Chua and colleagues 46 found that patients with pure anisometropic amblyopia were identified the latest of all patients with amblyopia.…”
Section: Risk Factors For Developing Amblyopia In Anisometropic Childrenmentioning
confidence: 99%